PERAN GURU DALAM MEMBENTUK KARAKTERISTIK (POLA PIKIR, POLA SIKAP, POLA TINDAK) SISWA GENERASI ALPHA - Siregar, Rozi; Aramudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has shaped the unique characteristics of Generation Alpha, requiring teachers to adopt adaptive roles in character development. This study aims to describe the role of teachers in shaping the characteristics of Generation Alpha students, including thinking patterns, attitudes, and behavioral patterns. The study employed a library research method by reviewing relevant scientific articles and literature on Generation Alpha, character education, and the role of teachers in the digital era. The findings indicate that teachers play an important role in developing students' critical thinking and digital literacy, fostering attitudes such as empathy, tolerance, responsibility, and digital ethics, and shaping positive behaviors through role modeling, habituation, social interaction, and responsible decision-making. These three dimensions are interconnected and serve as the foundation for developing the character of Generation Alpha students, enabling them to face the challenges of the twenty-first century wisely and responsibly.